1996
DOI: 10.1093/hmg/5.8.1101
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 11p15.5 regional imprinting: comparative analysis of KIP2 and H19 in human tissues and Wilms' tumors

Abstract: The imprinted H19 gene is frequently inactivated in Wilms' tumors (WTs) either by chromosome 11p15.5 loss of heterozygosity (LOH) or by hypermethylation of the maternal allele and it is possible that there might be coordinate disruption of imprinting of multiple 11p15.5 genes in these tumors. To test this we have characterized total and allele-specific mRNA expression levels and DNA methylation of the 11p15.5 KIP2 gene in normal human tissues, WTs and embryonal rhabdomyosarcoma (RMS). Both KIP2 alleles are exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 0 publications
5
77
2
Order By: Relevance
“…In this study, we demonstrated an antagonistic effect of FHL2 on Id2-driven proliferation of neuroblastoma cell types. The p57 Kip2 , IGF2 and H19 genes, belonging to the human chromosome 11p15.5-imprinted cluster, which have crucial functions in differentiation, the cell cycle and oncogenesis (46)(47)(48), are within the small group of E47-Id2 targets (27). In accordance with a previous report (27), we also demonstrated that the expression of these genes was strongly induced by E47 and inhibited by Id2.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we demonstrated an antagonistic effect of FHL2 on Id2-driven proliferation of neuroblastoma cell types. The p57 Kip2 , IGF2 and H19 genes, belonging to the human chromosome 11p15.5-imprinted cluster, which have crucial functions in differentiation, the cell cycle and oncogenesis (46)(47)(48), are within the small group of E47-Id2 targets (27). In accordance with a previous report (27), we also demonstrated that the expression of these genes was strongly induced by E47 and inhibited by Id2.…”
Section: Discussionsupporting
confidence: 91%
“…H19 expression has been shown to be drastically reduced in embryonal tumors due not only to loss of the maternal allele but also by extensive hypermethylation of both alleles' promoters in those tumors with maintenance of heterozyosity (MOH). 37,38 Hatada et al, 14 Thompson et al, 39 as well as Chung et al, 16 all reported clearly reduced expression of KIP2 in WTs, with Chung et al 16 even suggesting coordinate disruption of imprinting in WTs, having found H19 and KIP2 simultaneously reduced. However, our own results differ significantly from these findings.…”
Section: Discussionmentioning
confidence: 96%
“…10 -13 In addition, KIP2 is known to be expressed predominantly from the maternal allele 14,15 and its expression is significantly reduced in certain WTs and other embryonal tumors. 16 Thus, KIP2 is a candidate for the 11p15.5 tumor suppressor involved in HB. We, therefore, decided to screen a large series of HBs for KIP2 mutations and to determine the level of KIP2 mRNA expression in these tumors.…”
mentioning
confidence: 99%
“…It is plausible that the imprinting defect with loss of CpG methylation and loss of H3 Lys9 dimethylation causes a change of epigenotype of the KIP2/LIT1 region from maternal to paternal, reducing KIP2 expression. The relatively inactive paternal KIP2 promoter in normal human cells is not associated with either CpG methylation or H3 Lys9 methylation, implying that other epigenetic mechanisms must be involved in paternal KIP2 silencing [Chung et al, 1996;Higashimoto, unpublished results]. (However, it should be noted that the mouse Kip2 CpG island does show paternal-specific CpG methylation and H3 Lys9 dimethylation [Hatada and Mukai, 1995;Higashimoto, unpublished results].)…”
Section: Bws Regionmentioning
confidence: 99%